Work From Anywhere as a New Lifestyle: The Role of Work Flexibility, Work-Life Balance, and Job Satisfaction among Millennial Workers in Indonesia - Itto Turyandi; Andi Nenie Srilestari; Dyah Bayu Framesthi (International Journal Administration, Business & Organization, 2026)
Research on Work From Anywhere (WFA) has primarily examined it as a work arrangement, while its role as a lifestyle orientation remains underexplored, particularly in developing countries. This study investigates the effects of work flexibility on work-life balance, job satisfaction, and the internalization of WFA as a lifestyle among Indonesian millennials, while also exploring their lived experiences. A mixed methods sequential explanatory design was employed. The quantitative phase surveyed 247 millennial employees practicing WFA in Jakarta, Bandung, and Bali, with data analyzed using Partial Least Squares Structural Equation Modeling. The qualitative phase involved semi-structured interviews with 20 participants and thematic analysis. The findings indicate that work flexibility positively influences work-life balance, job satisfaction, and WFA as a lifestyle. Work-life balance and job satisfaction partially mediate the relationship between work flexibility and lifestyle internalization. Four qualitative themes emerged: personal autonomy, work-life integration, mobility as identity, and challenges related to social isolation and economic uncertainty. The study concludes that work flexibility supports the adoption of WFA as a lifestyle by enhancing work-life balance and job satisfaction. These findings extend understanding of WFA among Indonesian millennials and offer practical implications for developing adaptive workplace policies.